Pemeringkatan Supplier Kayu Lapis Menggunakan Metode Hibrid AHP-COPRAS - Adetya Septianingrum; Setyawan Wibisono (STEKOM PRESS, 2023)
Plywood is a processed product of several veneer sheets glued together perpendicularly. Plywood can be processed into various kinds of furniture, such as tables, chairs and so on. For furniture companies, plywood is one of the basic materials needed in the production process. Therefore, the company needs a plywood supplier that fits the company's criteria. The number of criteria in the selection of suppliers aims for the company to get optimal results. The following are the criteria that will be used in the study including price, material, thickness, grade and type. The biggest problem that ever happened to the company and resulted in a sizeable loss was that the supplier changed the raw materials used in the production process without the company's approval. In this study an application was designed that could assist in rating plywood suppliers using the AHP method and then using the COPRAS method. The supplier that gets the highest score after being processed using the AHP and COPRAS methods is the best supplier of plywood. Application designed in the form of a website. With this application, it can make it easier for users to choose plywood suppliers.